2017
DOI: 10.1002/asi.23883
|View full text |Cite
|
Sign up to set email alerts
|

Mendeley readership as a filtering tool to identify highly cited publications

Abstract: This study presents a large scale analysis of the distribution and presence of Mendeley readership scores over time and across disciplines. We study whether Mendeley readership scores (RS) can identify highly cited publications more effectively than journal citation scores (JCS). Web of Science (WoS) publications with DOIs published during the period 2004-2013 and across 5 major scientific fields have been analyzed. The main result of this study shows that readership scores are more effective (in terms of prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 55 publications
4
48
1
1
Order By: Relevance
“…To be confirmed in this research Mendeley readership and times cited (Priem et al, 2012;Zahedi et al, 2017). Nevertheless, the results of correlations between tweets and citation are controversy.…”
Section: Correlation Between Downloads and Citationssupporting
confidence: 52%
“…To be confirmed in this research Mendeley readership and times cited (Priem et al, 2012;Zahedi et al, 2017). Nevertheless, the results of correlations between tweets and citation are controversy.…”
Section: Correlation Between Downloads and Citationssupporting
confidence: 52%
“…These are mostly captures traced in Mendeley, a phenomenon that is generally applicable to all data record types. This corroborates earlier research, which found that Mendeley is one of the altmetrics data sources with the highest coverage (e.g., Zahedi et al, 2017).…”
Section: Resultssupporting
confidence: 92%
“…Compared to a similar broad prior study (Zahedi, Costas, & Wouters, 2017), the ratio of Mendeley readers to Scopus citations is about the same overall for publications from 2012: it is higher for newer articles (2013) and lower for older articles (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). The ratio of Mendeley readers to Scopus citations varied by disciplinary area with relatively few readers in Biomedical and Health Sciences and Natural Sciences and Engineering, and relatively many in social sciences and humanities (Zahedi, Costas, & Wouters, 2017).…”
Section: Discussionmentioning
confidence: 48%
“…Researchers may add an article to their Mendeley library at the time that they read it or even beforehand (Mohammadi, Thelwall, & Kousha, 2016), which largely removes the publication lag (Maflahi & Thelwall, 2016, in press;Thelwall & Sud, 2016;Thelwall, 2017a). Mendeley reader counts are suitable substitutes for citation counts because they correlate highly with them in many fields (Haustein, Larivière, Thelwall, Amyot, & Peters, 2014;Mohammadi, & Thelwall, 2014;Thelwall & Wilson, 2016;Zahedi, Costas, & Wouters, 2014;Zahedi, Costas, & Wouters, 2017), suggesting that they also indicate both scholarly influence and peer quality judgements. The latter has also been demonstrated directly (HEFCE, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation